Variations of antioxidant characteristics and mineral contents in pulp and peel of different apple (Malus domestica Borkh.) cultivars from Pakistan - Manzoor, Maleeha; Anwar, Farooq; Saari, Nazamid; Ashraf, Muhammad (MDPI, 2012)
Variations of phenolics, antioxidant activity, and mineral contents in peel and pulp of five apple (Malus domestica Borkh.) cultivars from Pakistan, namely Red Delicious, Golden Delicious, Kashmiri Amri, Kala Kulu and Sky Spur were appraised. The mean extract yield of antioxidant components obtained with 80:20 methanol-water (v/v), was found to be 22.1 g/100 g for peel and 14.2 g/100 g for pulp on a dry weight basis. The amounts of total phenolics and total flavonoids in peel and pulp of different cultivars of apple ranged from 1,907.5–2,587.9 mg gallic acid equivalent/100 g DW and 1,214.3–1,816.4 mg catechin equivalent/100 g DW and 1,185.2–1,475.5 mg GAE/100 g DW and 711.8–999.3 mg CE/100 g DW, respectively. The inhibition of linoleic acid peroxidation and DPPH scavenging activity of the extracts varied from 71.7–84.9 and 66.6–80.8% in peel, and 43.9–52.8 and 42.9–51.1% in pulp, respectively. Reducing power of the tested fruit part extracts at concentration 12.5 mg/mL ranged from 2.54–2.89 and 1.37–1.73, respectively. With regard to minerals analysis, both fruit parts showed the amount of K to be the highest, followed by Mg, Ca, Fe, Na and Zn. The results revealed that peel of the tested apple cultivars in this study had superior antioxidant capacity and mineral concentration than the pulp, indicating significant variations between the parts tested. Thus, consumption of apple fruits along with peel might be recommended to gaining better nutritive benefits.